Distinct TB-antigen stimulated cytokine profiles as predictive biomarkers for unfavorable treatment outcomes in pulmonary tuberculosis - Pandiarajan, Arul Nancy; Kumar, Nathella Pavan; Selvaraj, Nandhini; Ahamed, Shaik Fayaz; Viswanathan, Vijay; Thiruvengadam, Kannan; Hissar, Syed; Shanmugam, Sivakumar; Bethunaickan, Ramalingam; Nott, Sujatha; Kornfeld, Hardy; Babu, Subash (Frontiers in Immunology, 2024)
The assessment of tuberculosis (TB) treatment outcomes predominantly relies on sputum culture conversion status. To enhance treatment management, it is crucial to identify non-sputum-based biomarkers that can predict unfavorable outcomes. Cytokines are widely studied as diagnostic biomarkers for active TB. However, their potential as indicators for unfavorable treatment outcomes remains uncertain.Methodology: This study was conducted within a well-characterized cohort comprising newly diagnosed, drug-sensitive pulmonary TB patients, confirmed through sputum smear and culture positivity. Our objective was to elucidate the TB antigen-stimulated cytokine profile at pre-treatment and at two months into anti-TB treatment (ATT) in patients with unfavorable treatment outcomes (cases, n=27) in comparison to recurrence-free, microbiologically cured controls (n=31). Whole blood was stimulated with TB antigens using the QuantiFERON Intube gold method, and plasma supernatants were subjected to a panel of 14 cytokine measurements.Results: In our study, pre-treatment analysis revealed that eight cytokines (IL-2, IFN-γ, TNFα, IL-6, IL-10, IL-17A, IL-18, and GM-CSF) were significantly elevated at baseline in cases compared to cured controls, both in unstimulated conditions and following TB antigen (CFP10, ESAT6, and TB7.7) stimulation. A similar pattern was observed at the two-month mark of ATT, with eight cytokines (IL-2, IL-10, IL-13, IFN-γ, IL-6, IL-12p70, IL-17A, and TNF-α) showing significant differences between the groups. Importantly, no variations were detected following mitogen stimulation, underscoring that these distinctive immune responses are primarily driven by TB-specific antigens.Our findings indicate that individuals with unfavorable TB treatment outcomes display a characteristic cytokine profile distinct from TB-cured patients, even before commencing anti-TB treatment. Therefore, the levels of specific cytokines pre-treatment and at the two-month point in the course of treatment may serve as predictive immune markers for identifying individuals at risk of unfavorable tuberculosis treatment outcomes, with these responses being predominantly influenced by TB-specific antigens.